Profile of Physical Education Implementation in Elementary Schools - Muhamad; Mustika Fitri (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Education comprises all learning experiences that occur throughout life (lifelong education) and contribute positively to an individual’s physical and spiritual development. Physical education (PE) plays a crucial role in enhancing students’ motor skills, healthy lifestyle, social interaction, and mental well-being. This study aimed to determine the implementation profile of physical education learning in elementary schools across Regol District, Bandung City. Employing a descriptive quantitative design, the study involved a total sampling of 22 PE teachers. Data were collected using the Learning Supervision Questionnaire and analyzed using descriptive statistics with SPSS 25. The findings revealed a mean score of 90.59, indicating a “Very Good” category in PE learning implementation. Specifically, 55% of respondents achieved “Very Good” scores, and the remaining 45% were in the “Good” category, with no schools rated as “Fair” or “Poor”. These results reflect a consistently high standard of physical education teaching across the district. This study concluded that the implementation of physical education learning in elementary schools across Regol District is highly effective.